Implementation of the Non-Cash Food Assistance Program (PBPNT) George R. Terry's Management Function Perspective during the Pandemic Period in Tambakrejo Village, Jombang - Amin Awal Amarudin; Abdul Khorib (INCOME: Innovation of Economics and Management, 2022)
This research is motivated by the phenomenon of the Distribution of the Non-Cash Food Assistance Program (BPNT), which seeks to alleviate poverty, assist and strengthen food security, and facilitate control, monitoring and reduction of social deviance. The cooperation program between the Regional Social Service and the Village Government is carried out through non-cash procedures or through banking. The purpose of this research is to find out: 1). Implementation of PBPNT Implementation, 2). Constraints or obstacles faced, and 3). Alternative solutions to overcome obstacles. This type of research is descriptive qualitative research. Data collection techniques through observation, interviews and documentation. Data analysis techniques with data reduction, data presentation and drawing conclusions. The research location is Tambakrejo Village, Jombang. The implementation of PBPNT was analyzed from the perspective of management functions according to George R. Terry, namely; Planning, Organizing, Actuating, and Controling. Research results: 1). The implementation of PBPNT Tambakrejo in terms of distribution is in accordance with procedures, the distribution is carried out on target, in the right quantity, at the right price and quality and in proper administration, it just needs to be improved on the delivery time. Implementation is in accordance with George R. Terry's perspective management functions in terms of Planning, Organizing, and Actuating, only at the Controling stage it needs to be optimized because there is no special agency from the village apparatus assigned to handle this program. 2). Regarding program constraints, there were no serious problems that resulted in the failure of distribution. The technical problems encountered were missing cards, error cards, cards that had not been updated and food rations that had not been taken according to the stipulated time. 3). The solution to these problems is by calling the recipient or coordinating the recipient with the officer, updating the card, repairing the error card, and giving double quota for people who are late in taking it.